Cognitive Process of Pre-service Science Teachers Using Problem-based Learning on Nervous System Concepts - Hodijah, Siti Romlah Noer; Rahmat, Adi; Priyandoko, Didik; Wahyudin, Wahyudin (Jurnal Penelitian dan Pembelajaran IPA, 2023)
Cognitive Process (CP) is a mental process that occurs when a person forms new knowledge with fully conscious or unconscious actions. This study aimed to obtain an overview of the CP of students who are pre-service science teachers in learning the nervous system using a problem-based learning model. The sample of the research was 37 student pre-service science teachers, who were taking the 4th semester. Students’ CP is measured using a CP instrument that refers to Marzano’s taxonomy. Data is analyzed by looking at the average value and frequently occurring answers, then interpreting the findings with the underlying theory. The description of 4th semester pre-service students in science education on nervous system concepts shows that the ability to think in the cognitive system has not been well formed compared to the ability to believe in the metacognitive system and self-system. Based on these conditions, developing more appropriate learning strategies to develop the CP of science teacher candidates is still necessary.